2021
DOI: 10.1016/j.cbd.2021.100889
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals key genes and pathways associated with egg production in Nandan-Yao domestic chicken

Abstract: BackgroundEgg production is a very important economic trait in chicken breeding, but its molecular mechanism is unclear until now. Nandan-Yao chicken (Gallus gallus domesticus) is a native breed in Guangxi province, China, which is famous for good meet quality, but low egg production. To explore the molecular regulation related egg production, high egg production (HEP) and low egg production (LEP) were divided according to the total egg number at 50 weeks, and the concentration of serum sex hormones was tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Zhang et al [ 22 ] found the pathway correlated with eggshell quality in chickens. The high DEGs in the “cytokine–cytokine receptor interaction” in this study coincided with reports on egg production in Nandan-Yao domestic chicken and Muscovy duck [ 23 , 24 ]. In brief, the three pathways, “neuroactive ligand–receptor interaction”, “calcium signaling pathway”, and “cytokine–cytokine receptor interaction” are considered to be closely related to chicken egg production performance.…”
Section: Discussionsupporting
confidence: 89%
“…Zhang et al [ 22 ] found the pathway correlated with eggshell quality in chickens. The high DEGs in the “cytokine–cytokine receptor interaction” in this study coincided with reports on egg production in Nandan-Yao domestic chicken and Muscovy duck [ 23 , 24 ]. In brief, the three pathways, “neuroactive ligand–receptor interaction”, “calcium signaling pathway”, and “cytokine–cytokine receptor interaction” are considered to be closely related to chicken egg production performance.…”
Section: Discussionsupporting
confidence: 89%
“…In duck's ( 6 ), goose's ( 21 ), and goat's ( 22 ) ovary transcriptome studies, the actin cytoskeleton has been discovered to be related to ovary function. The phagosome and cell adhesion molecules (CAMs) were consistently reported in a study comparing the ovary of high- and low-laying ducks ( 23 ). Overall, these signaling pathways may control ovary development and may be involved in the egg production of Gaoyou duck.…”
Section: Discussionmentioning
confidence: 81%
“…In the present study, most DEGs and DELs possessed nonadditivity pattern in hybrids, indicating nonadditivity was the critical gene expression pattern affecting traits heterosis. Functional enrichment analysis showed that nonadditive genes were associated with animal organ development, female gonad development, ECM-receptor interaction and GnRH signaling pathway, such as laminin subunit alpha 4 (VTN), CD36 molecule (CD36) and fibronectin 1 (FN1), which were revealed to function in ovary cell growth and proliferation (49)(50)(51) and specifically expressed in crossbreeds' ovary. In addition, the nonadditive gene purinergic receptor P2X 1 (P2RX1) was identified, which was enriched in calcium signaling pathway.…”
Section: Discussionmentioning
confidence: 99%